A Reading Through Examples of Iraqi Novels The Body of Women As a Specimen - سها صاحب القريشي أ. م. د. (lark, 2020)
We live in an era where the literary people showing lots of interests in interpreting it’s action and framing its facts, or imagining possible facts which are possible to turn into reality, using a method which is one of the most widespread means; due to it’d ability to cut-short scenes as big as the world, and the author cut from specific time and place to narrate it in influential artistic literary method of a reformist nature. Although the novel generally discussing the subjects of identity, belonging, and life difficulties facing man, but the most prominent theme in the novels of Mahmood Saeed is concentrating on the Eros dimension among all the subjects which are associated with woman body, and how the reflection of life and political defeats reflects on practicing it, using descriptions indicating his eagerness to show them more than other elements, while we find novels where he evoke the body of woman in more realistic and touching to the life circumstances in the novels of Hadeya Hussain, whom the research has taken examples from them with other examples of Mahmood Saeed novels as subjects of study through two dialogues starting with introductory and ending with conclusion.